Additions to the trigonalyid (Hymenoptera: Trigonalyidae) fauna of India with the description of a new species from south India - Femi, Ezhuthupallickal Benny; Ranjith, Avunjikkattu Parambil; Priyadarsanan, Dharma Rajan (Zootaxa, 2024)
A new species of Taeniogonalos is described and illustrated from Western Ghats, Kerala, India. The male of Taeniogonalos eurysoma Chen & van Achterberg, 2020 is described for the first time along with its first distribution record from India. The new species and T. eurysoma are illustrated along with a distribution map of Indian Taeniogonalos.